Reducción de efluentes coloreados de la empresa “CURTIPIEL CASTRO”, Provincia de Tungurahua utilizando minerales arcillosos - Obando Reinoso, Jennifer Alejandra (2017)
The leather industry is one of the activities that consumes more water and generates large amounts of gaseous, liquid and solid waste; it is also an important source of contaminated liquid effluents that change the properties of water especially in color, pH, turbidity and total suspended solids. The present work analyzed the colored effluents of the "CURTIPIEL CASTRO" company and the pigments used for the processes of dyeing the leather. In the investigated industry there is no effluent treatment that helps to minimize the pollution produced by the carbon black dye. Therefore, the main objective of this work was to reduce the colored effluents from the "CURTIPIEL CASTRO" company, using two types of clay minerals with two types of quaternary salts obtaining four test treatments (M1, M2, M3, M4), Which allowed to identify the best dye reduction treatment that can be used in the company to satisfy with the current environmental regulations. In order to determine the exact concentrations in the tests M1 (aluminum sulfate and bentonite), M2 (aluminum polychloride and bentonite), M3 (aluminum polychloride and black clay), M4 (aluminum sulfate and black clay) concentrations which were used in previous experiments were applied where the